- ~(Access) → Polluted
Access
⊢
~(Polluted)
The fallacy here is quite clear and I do believe we call it a false negation. Basically, what is going on here is that we are given a sufficient condition and a necessary condition, concluding that a negation of the sufficient condition will equal a negation of the necessary condition. This is, obviously, not logical and we want to find something that does the same. We want to find something that says X → Y, therefore ~X → ~Y
(A) This is actually logically perfect. No flaw here. This answer choice is merely giving us a contrapositive.
- Full Moon → Higher Tide
~Higher Tide
⊢
Full Moon
(B) This is what I do believe we call a mistaken reversal. This answer choice gives us a conditional and then states that when the necessary condition happens, the sufficient condition happens. It looks like this:
- Stole $$$ → Conspicuous Spending
Conspicuous Spending
⊢
Stole $$$
There could absolutely be other reasons for spending money conspicuously rather than stealing money.
(C) This looks very good and it seems to give us the mistaken reversal we were looking for! As an added bonus, it discusses masses of people rather than one single person, as the stimulus also does.
- Solitary Confinement → Increased Violence
~(Solitary Confinement)
⊢
~(Increased Violence)
Perfect!
(D) This is logically the same as (B).
(E) This is logically the same as (B).